Kajian Yuridis Terhadap Pembagian Harta Warisan Pada Perkawinan Beda Agama - Vaengky Azmur; Aksah Kasim; Andi Heridah (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
This study aims to determine and understand the status of interfaith marriages by comparing Civil Law and Islamic Law. And also to find out the division of inheritance in interfaith marriages according to Civil Law and Islamic Law. This research uses a type of normative research supported by a case study approach (case approach), and an analytical approach (Analytical Approach). The results of the study show that the status of interfaith marriages is invalid from the point of view of civil law and Islamic law. The researchers also show that the method of dividing inheritance in interfaith marriages is seen from the perspective of civil law and Islamic law, in Islamic law inheritance is not given to people who are not Muslims because of a barrier to inheritance, namely religious differences. whereas in Civil Law the distribution of inheritance can be given to someone regardless of religious differences.